Nonnegligible pathogenic exposure risk of coarse part of PM10 in non-open environments - Zhao, Yirong; Mao, Kang; Cao, Haorui; Wang, Bin; Zheng, Xingli; Du, Wei; Zhang, Xiangyan; Zhang, Hua (Frontiers in Environmental Science, 2022)
In non-open environments, pathogenic microorganisms are more likely to invade the human respiratory tract due to their limited diffusion in the environment, which has received little attention. In this study, we explored the distribution characteristics of particulate matter (PM) in non-open environments, and included sewage treatment plants and farms, which are occupational exposure risks, and G-series high-speed trains and waiting rooms, which are crowded. The results showed orders of magnitude differences in PM and microbial concentrations and the DNA/PM values of adsorption in the different non-open spaces. The concentration of PM with a size in the 4.7-10.0 μm range was higher than those of PM in the 1.1-4.7 μm and 0.43-1.1 μm ranges in all three types of places, accounting for 74.64%, 46.59% and 51.49%, respectively. The DNA/PM value for the 1.1-4.7 μm range was higher than those for PM in the other two ranges in all three types of places at 0.175, 3.78×10-3, and 9.98 ng/μg, respectively. Although the relative abundances of Class II potentially pathogenic bacteria with sizes ranging from 1.1 to 4.7 μm were higher in all three types of places, the total abundance and the relative abundance of identified pathogenic microorganisms with sizes ranging from 4.7 to 10.0 μm were higher in all three types of places. Here, in non-open spaces, the pathogen exposure risk associated with PM10, particularly the coarse fraction of PM10, deserves special attention. Infectious diseases caused by aerosol transmission of pathogens in non-open environments should receive more attention and require further investigation in the future.